Dental neglect and dental health among 26-year-olds in the Dunedin Multidisciplinary Health and Development Study - Thomson WM, Locker D (Blackwell Synergy, 2000)
To test a modification of a previously-reported six-item dental neglect scale and examine its association with dental health and service-use among young adults. Methods: Of the 980 26-year-old participants in the Dunedin Multidisciplinary Health and Development Study, 973 completed the scale and 930 underwent dental examination. Sociodemographic and dental service-use data were collected using a self-report questionnaire.